Local modulation and trapping of energetic particles by coherent magnetic structures. Issue 8 (18th April 2016) - Tessein, Jeffrey A.; Ruffolo, David; Matthaeus, William H.; Wan, Minping
Abstract: Recent observational studies show strong statistical associations between features of interplanetary suprathermal energetic particle (EP) data and rapid changes in the interplanetary vector magnetic field. The latter are connected to intermittency and coherent magnetic structures, including classical discontinuities. Here we discuss these observations in the context of two appealing theoretical ideas: First, magnetic structures bounding flux tubes can cause local or temporary topological trapping, thus influencing EP transport. Second, charged particles may be accelerated by interacting with dynamic flux tubes, either through reconnection, trapping in secondary islands, or a betatron mechanism. We present observations that support interpretation in terms of trapping boundaries associated with changes in EP flux and also find a case in which an EP peak lies near a coherent magnetic structure that is not a shock, with changing particle anisotropy consistent with outflow from the structure, suggestive of local particle acceleration. Key Points: Association of EPs and magnetic structures is related to flux tube structure Particles may be temporarily trapped in flux tubes, influencing transport Particles may be accelerated by flux tube dynamics (reconnection, secondary islands, and betatron)